Kwaidan [videorecording (DVD)] - Kobayashi, Masaki, 1916-1996; Aratama, Michiyo; Watanabe, Misako, 1932-; Mikuni, Rentarō, 1923-2013; Hearn, Lafcadio, 1850-1904 (Criterion collection, 2015)
After more than a decade of sober political dramas and social-minded periodpieces, the great Japanese director Masaki Kobayashi shifted gears dramatically for this rapturously stylized quartet of ghost stories. Featuring colorfully surreal sets and luminous cinematography, these haunting tales of demonic comeuppance and spiritual trials, adapted from writer Lafcadio Hearn's collections of Japanese folklore, are existentially frightening and meticulously crafted. In The black hair, a poor young samurai leaves his first wife to marry a rich woman. When he is unhappy in his second marriage, he returns to his first wife, who at first appears unchanged from when he last saw her. In The woman of the snow, a woodcutter is spared by a mysterious ghost-like woman in the snow, but must promise never to tell anyone what he has seen. In Hoichi, the earless, a blind musician-monk named Hoichi is commanded by a gathering of ghosts to sing the saga of their ancient deeds. The head monk paints Hoichi's body with prayer verses to protect him, but unfortunately overlooks Hoichi's ears. In In a cup of tea, a writer wonders what would happen to a person who drinks another's soul and finds out.